Precarity: causes, effects and consequences of insecure working and living conditions in a multicultural, rural area of northern Italy (South Tyrol) - Tschöll, Christine (Journal of Education Culture and Society, 2020)
The research project deals with the current issue of precarity, its mechanisms, risks, effects, coping strategies as well as coping competences and addresses the impact of work-based insecurities, rising social inequalities within and across nations, with a specific regional focus on South Tyrol - a multicultural, rural area in northern Italy, bordering with Austria. Finally, it is important to identify possible innovative solutions for the labour market, Human Resources strategies and social policies. The concept of work will be related to all securitized fundamental rights, their socialization context, the global change of values and the social change in the welfare state. The recent transformation from discourses on inequality and poverty towards social exclusion and inclusion indicates a conceptual shift in the societal management of social inequalities. The global financial crisis has highlighted the connectedness between corporate and household risk behaviour and management, and their socially inequitable effects. The interdisciplinary view enables a focus on multiple insecurities and how they interact to produceprecarious work relations, in reference to working conditions and the experience of social exclusion, the links between de-regulation, liberalization and the individualization of employment risks, but also the development of interest representation and social organizations for supporting labour market outsiders. The paper describes the current process of defining the research design, preliminary reflections for the case study and shows first outcomes of the project.